(untitled) (Raparin Journal of Humanities (RJH), 2023)
This research deals with the efforts of a prominent Scientist of the Haidari family, who served Islam for nearly three hundred years, and stayed up nights in order to receive the satisfaction of Allah Almighty, they wrote many books on various sciences and fields which they left a great legacy, so if we compare their books with their lives, it is clear that they did not fulfill their age in vain. Among those Scientists is Ibrahim bin Haider al-Haidari (died: 1157 AH), may Allah have mercy on him-who compiled many books of science related to theology, which is considered as a basis of religion, and also in the interpretation of the Holy Qur’an through two parts, but it did not remain and became one of its lost traces, this research in question deals with the approach and opinions of the researcher Ibrahim bin Haider Al-Haydari through his elucidation of the Surat Al-Ikhlas which amends one-third of the Qur’an. Through his explanation of this surah, al-Haidari clarified the aspects related to faith and explained them in terms of language, logic, mysticism, and Sufism.